2009
DOI: 10.2310/jim.0b013e3181b91bbd
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Endothelial Nitric Oxide Synthase Gene Polymorphisms in Turkish Population

Abstract: Nitric oxide (NO) is the major mediator in the regulation of vascular homeostasis. It is synthesized by endothelium from arginine with the catalytic help of endothelial NO synthase (eNOS). Polymorphisms in the eNOS gene have been associated inconsistently with many vascular diseases. Conflicting results may arise from ethnic variations, notably in control-case studies. Therefore, to obtain reliable information and improve the design of such genetic association studies, we examined the distribution of genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Of note, we and others had previously reported that there was no deviation in T/G allele frequencies from the Hardy-Weinberg equilibrium in the HF patient group compared to the healthy control group, genotype frequencies reported in the Single Nucleotide Polymorphism Database (dbSNP), or other ethnic groups [34,40].…”
Section: Resultsmentioning
confidence: 98%
“…Of note, we and others had previously reported that there was no deviation in T/G allele frequencies from the Hardy-Weinberg equilibrium in the HF patient group compared to the healthy control group, genotype frequencies reported in the Single Nucleotide Polymorphism Database (dbSNP), or other ethnic groups [34,40].…”
Section: Resultsmentioning
confidence: 98%
“…However, when the relationship between the G894T polymorphism of the eNOS gene between the case and control groups with both male and female genotypes was evaluated in our study, no statistical difference was found. Sinici et al (2009) investigated G894T polymorphism in the Turkish population and its correlation with vascular disease and also did not find a significant correlation between male and female. Gad et al (2012) also found no statistical difference between male and female that could contribute to a greater influence on the polymorphism on the Egyptian population.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, marked differences in both genotype and haplotype frequencies of NOS3 exist between ethnicities, which could explain some of the discrepancies between studies. 26,28 The etiology behind the sex differences in SAH patients remains unknown. Earlier studies indicate that women have higher blood flow velocities, especially in the posterior circulation, and that autoregulation of cerebral blood flow may function differently in men and women under some circumstances such as orthostatic stress.…”
Section: Discussionmentioning
confidence: 99%